KAJIAN SOSIOLINGUISTIK VARIASI BAHASA BERDASARKAN USIA PENUTUR PADA KESENIAN BLUK GEBLUK REMBANG PASURUAN - Adib Fanani, Muhammad; Windu Asrini, Hari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines language variation based on speaker age in the Bluk Gebluk traditional art of Rembang, Pasuruan, using a sociolinguistic approach. This traditional art takes the form of reciting syi'iran in Madurese and Javanese languages, functioning as a medium for Islamic da'wah. The phenomenon of language variation between the older generation (jam'iyah women) and the younger generation (elementary and junior high school students) is the main focus of this research. The objectives of this study are to describe the forms of language variation, identify the causal factors, and analyze the functions of language variation based on differences in speaker age. This research employs a descriptive qualitative method with data collection techniques including participatory observation, in-depth interviews, and documentation. Data were analyzed through data reduction, data display, verification, contrastive analysis, and thematic analysis. The results show that language variation occurs at three linguistic levels: lexicon (word choice), phonology (sound system), and morphology (word formation). The factors causing language variation include internal factors (age, education, language proficiency), external social factors (family environment, media), and situational factors (religious study context vs. art competition context). Language variation in Bluk Gebluk traditional art serves six functions: educational, da'wah, cultural preservation, social, identity, and aesthetic functions. This research contributes to the development of sociolinguistic studies, particularly language variation based on speaker age in traditional arts.